Społeczna percepcja energetyki jądrowej w perspektywie procesów transformacji energetycznej w Polsce - Herudziński, Tomasz (Człowiek i Społeczeństwo, 2021)
The article analyzes the attitude of the Polish society to nuclear energy as an important energy source in the future and emphasizes the social dimension of the processes, by relating them to the sociology of energy. The attitude to nuclear energy is presented in comparison to other conventional and non-renewable energy sources, such as coal, oil or gas as well as renewable energy sources (RES) obtained from the sun, air or water. The ways of thinking and fears of the Polish society towards nuclear energy are presented in relation to the processes of energy transformation in Poland. The author indicates the main assumptions of the energy transformation and presents social ideas about the future of the energy sector in Poland. In the empirical dimension, the article concerns the sphere of social awareness and uses the results of surveys conducted by the Public Opinion Research Center (CBOS) in the period from 1987 to 2021.